A weather-resistant high-viscosity single-component composite glue, preparation method and application in multi-layer structure car cover
By preparing a weather-resistant, high viscosity single-component composite glue containing high-performance polyurethane prepolymer and multifunctional nanofiller, the problems of short service life and insufficient weather resistance of the existing glue are solved, and the long-term stability and high adhesion of the glue are achieved.
Patent Information
- Application Number
- CN202411718449.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing composite glue has a short service life, and there is a problem of insufficient weather resistance in multi-layer structure car clothing, which affects the service life and performance of the product.
A high-performance polyurethane prepolymer is formed by using a weather-resistant and high-viscosity single-component composite glue. Acrylic acid is prepared by using rosin and acrylic acid as raw materials, and reacting with 4,4'-dithiodianiline, combining magnolol derivatives and modified polypropylene glycol to form a high-performance polyurethane prepolymer, and multifunctional nanofillers are added to improve the weather resistance and adhesion of the glue.
The glue is achieved for a long time stability and high viscosity, which improves its adhesion and weather resistance in multi-layer structural car clothing, extends the service life of the product, and improves the overall performance.
Smart Images

Figure CN119193089B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a weather-resistant high-viscosity single-component composite glue, a preparation method and application in multi-layer structure car covers. Background Art
[0002] TPU color-changing film is made of TPU in various colors and textures, so that its appearance can be as complex and diverse as the color variety. Its function is the same as invisible car cover, which can protect the car paint from scratches. With the development of technology and process innovation, there are now a wide variety of TPU color-changing films on the market. There are three main types of structures and manufacturing processes: PVC & TPU laminating film, TPU substrate + liquid TPU color layer, and TPU double-layer co-extruded real paint film. However, they all have certain disadvantages:
[0003] (1) PVC & TPU laminating film: Poor protective performance: In order to make the product fit tightly and be installed smoothly, the thickness of the two main base materials of the product has been weakened; easy to delaminate: TPU and PVC have different ductility, and the two are easy to delaminate after laminating; short service life: the warranty period of conventional PVC color-changing film is 1-2 years, while the warranty period of TPU car cover is generally more than 5 years;
[0004] (2) TPU substrate + liquid TPU color layer: TPU liquid coloring is relatively complicated and the yield is low, so the production cost is relatively high; the colors are limited to some conventional monochrome crystal series;
[0005] (3) TPU double-layer co-extruded lacquer film: The main reason why this technology has not been widely popularized is the equipment cost. Because it is a TPU double-layer co-extruded, one device needs to be equipped with two upper and lower extrusion die heads, which is expensive.
[0006] In order to solve the above problems, a color-changing car cover with a multi-layer structure has also appeared. Its structure from top to bottom is PET substrate layer, repair layer, TPU substrate layer 1, composite glue layer, TPU substrate layer 2, installation layer and release film layer; the performance of the composite glue layer has an important influence on the overall performance of the color-changing car cover. At present, the glue used in the composite glue layer is mainly two-component glue, that is, the main agent is bifunctional polyurethane, and the curing agent is isocyanate curing agent. The cross-linking structure is generated by the reaction of the main agent and the curing agent to produce excellent interlayer adhesion. However, the use of two-component composite glue is time-limited, that is, the main agent and the curing agent must be used up within 4 hours after being mixed and stirred evenly. On the one hand, the performance of the composite glue will change greatly if the time limit is exceeded, which will affect the product performance. On the other hand, it will cause unnecessary losses. In addition, since the car cover is exposed to the external environment, in order to ensure the effect of the glue layer and extend the service life of the car cover, it is also very necessary to improve the weather resistance of the glue layer (high temperature resistance, moisture resistance, and UV resistance). Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a method for preparing a weather-resistant high-viscosity one-component composite glue, comprising the following steps:
[0008] Step (1), using rosin and acrylic acid as raw materials to prepare acrylopimaric acid; acrylopimaric acid is modified by chlorination and then reacted with 4,4'-dithiodiphenylamine to obtain an intermediate product A;
[0009] Step (2), magnolol reacts with 3-mercaptopropionic acid to obtain a magnolol derivative; hydroxymethylcoumarin reacts with 3,5-diaminobenzoic acid to obtain an intermediate product B; and the intermediate product B reacts with a magnolol derivative to obtain an intermediate product C;
[0010] Step (3), intermediate product A reacts with intermediate product C to obtain intermediate product D; intermediate product D reacts with 1-(2-oxirane-1)ethane-1,2-diol to obtain functionalized bio-based polyol;
[0011] Step (4), reacting perfluorooctanoyl chloride with 2-amino-2-methyl-1,3-propanediol to obtain a fluorine-containing compound; and reacting polypropylene glycol with the fluorine-containing compound after carboxylation to obtain modified polypropylene glycol;
[0012] Step (5), using modified polypropylene glycol, functionalized bio-based polyol and isophorone diisocyanate as raw materials to prepare a high-performance polyurethane prepolymer; mixing the high-performance polyurethane prepolymer, high-acid value acrylic resin, cellulose acetate butyrate, SBS rubber, multifunctional nanofiller, solvent and latent curing agent, and sealing and storing at low temperature to obtain a weather-resistant high-viscosity single-component composite glue; wherein the preparation method of the multifunctional nanofiller comprises the following steps: step S1, preparing composite nanoparticles, and modifying them by γ-aminopropyltriethoxysilane to obtain surface-modified composite nanoparticles; step S2, modifying graphene oxide by thionyl chloride, and combining it with the surface-modified composite nanoparticles to obtain an inorganic composite nanomaterial; reacting the inorganic composite nanomaterial with 1,2-epoxy-5-hexene to obtain a surface-modified inorganic composite nanomaterial; reacting the surface-modified inorganic composite nanomaterial with trimethoxysilane to obtain a multifunctional nanofiller.
[0013] Preferably, in the step (1), the preparation method of the intermediate product A is as follows: rosin and hydroquinone are mixed, and the temperature is raised to 230-240°C at a rate of 5-10°C / min in a nitrogen atmosphere, and acrylic acid is then added dropwise at a rate of 0.8-1.2 mL / min. After the addition is completed, the temperature is kept constant for reaction for 3-4 hours. After the reaction is completed, the nitrogen flow rate is increased, the temperature is lowered to 170-180°C, the material is discharged, cooled to room temperature, ground, washed, and dried to obtain propylene pimaric acid; wherein the mass ratio of rosin, hydroquinone, and acrylic acid is (60-100): (0.2-0.5): (15-30); propylene pimaric acid and triethylamine are added to tetrahydrofuran and mixed until uniform, and then oxalyl chloride is added, and the mixture is stirred at 4-6°C for 20 minutes. -40min, then stirred at 28-32℃ for 2.5-3.5h. After the reaction, purified to obtain acyl chloride modified acrylpimaric acid; wherein the mass ratio of acrylpimaric acid, triethylamine, tetrahydrofuran and oxalyl chloride is (15-25): (0.1-0.15): (200-300): (20-40); 4,4'-dithiodiphenylamine was added to N,N-dimethylformamide and mixed until uniform, then acyl chloride modified acrylpimaric acid was added, heated to 85-95℃ for reaction for 20-28h. After the reaction, rotary evaporation was performed to obtain intermediate product A; wherein the mass ratio of 4,4'-dithiodiphenylamine, N,N-dimethylformamide and acyl chloride modified acrylpimaric acid is (6.2-12.4): (100-1 50): (4.9-9.8); In the above process, hydroquinone is used as an inhibitor, rosin and acrylic acid react to obtain acrylopimaric acid; the carboxyl group in acrylopimaric acid reacts with oxalyl chloride to be chlorinated to obtain chlorinated modified acrylopimaric acid; the acyl chloride of chlorinated modified acrylopimaric acid reacts with the amino group of 4,4'-dithiodiphenylamine to obtain an intermediate product A, which contains an amino group, a dynamic disulfide bond, an amide bond and a rigid hydrogenated phenanthrene ring from rosin; Preferably, in the step (2), the preparation method of the intermediate product C is as follows: magnolol is added to ethanol, ultrasonically treated for 20-40 min, heated to 60-70°C, and then 3-mercaptopropionic acid and a 0.5wt% azobisisobutyronitrile / ethanol solution are added, stirred and reacted. The mixture was stirred for 3-5 hours, filtered, washed and dried to obtain a magnolol derivative; wherein the mass ratio of magnolol, ethanol, 3-mercaptopropionic acid and azobisisobutyronitrile / ethanol solution was (5.3-10.6): (200-300): (3.5-5.5): (15-20); hydroxymethylcoumarin, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and N,N-dimethylformamide were mixed, heated to 120-140°C in a nitrogen atmosphere, stirred and reacted for 3-5 hours, and purified after the reaction to obtain an intermediate product B; wherein the mass ratio of hydroxymethylcoumarin, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and N,N-dimethylformamide was (8.8-17.6): (7.6-15.2): (0.07-0.1): (120-150); add magnolol derivatives to ethanol, ultrasonically treat for 20-40min, add N'N-dicyclohexyl diimide and N-hydroxysuccinimide, stir for 1-2h, then add intermediate B under stirring, stir and react at room temperature for 22-26h in a nitrogen atmosphere, adjust the pH of the reaction system to 5.4-5.6 with a 1mol / L hydrochloric acid aqueous solution during the reaction, filter, wash and dry to obtain intermediate C; wherein magnolol derivatives, ethanol, N'N-dicyclohexyl diimide The mass ratio of amine, N-hydroxysuccinimide and intermediate product B is (4.8-9.6): (80-120): (3.7-7.4): (2.1-4.2): (6.2-12.4); in the above process, the double bond of magnolol reacts with the thiol group of 3-mercaptopropionic acid to obtain a magnolol derivative containing carboxyl groups at both ends; hydroxymethylcoumarin and 3,5-diaminobenzoic acid are combined by esterification reaction to obtain intermediate product B; the carboxyl group of the magnolol derivative reacts with the amino group of intermediate product B to obtain intermediate product C, which contains magnolol structure, amide bond and Coumarin ring, the coumarin ring can undergo a reversible cycloaddition reaction under ultraviolet light irradiation or heating conditions; preferably, in the step (3), the preparation method of the functionalized bio-based polyol is as follows: adding the intermediate product A to N,N-dimethylformamide, then adding glutaraldehyde, heating to 90-98°C for reaction for 9-11h, then adding the intermediate product C, continuing to stir and react for 10-16h, after the reaction is completed, rotary evaporation is performed to obtain the intermediate product D; wherein the mass ratio of the intermediate product A, N,N-dimethylformamide, glutaraldehyde, and the intermediate product C is (8.2-16.4): ( 200-300): (1.5-4.5): (10.4-20.8); add the intermediate product D to N,N-dimethylformamide, stir for 20-40 minutes, then add 1-(oxirane-2-yl)ethane-1,2-diol, heat to 60-80°C and stir for 16-24 hours, rotary evaporate, wash, and dry to obtain functionalized bio-based polyols; wherein the mass ratio of the intermediate product D, N,N-dimethylformamide, and 1-(oxirane-2-yl)ethane-1,2-diol is (10-20): (200-300): (3.5-5.5); In the above process, glutaraldehyde is used as a cross-linking agent, and the two aldehyde groups of glutaraldehyde react with the amino groups at one end of the intermediate product A and the intermediate product C to form an imine bond to obtain an intermediate product D; the amino group of the intermediate product D then reacts with the epoxy group of 1-(ethylene oxide-2-yl)ethane-1,2-diol to obtain a functionalized bio-based polyol containing multiple hydroxyl groups; Preferably, in the step (4), the preparation method of the modified polypropylene glycol is as follows: polypropylene glycol is added to dichloromethane, and then maleic anhydride and 4-dimethylaminopyridine are added, and the reaction is stirred at room temperature for 70-80 hours. After the reaction is completed, the product is precipitated with ether, washed, and dried to obtain dicarboxylated polypropylene glycol; wherein polypropylene glycol, dichloromethane, and maleic anhydride are , 4-dimethylaminopyridine is in a mass ratio of (10-20): (200-300): (4-7): (0.05-0.1); in a nitrogen atmosphere, perfluorooctanoyl chloride is added to tetrahydrofuran, and then a 0.2 g / mL 2-amino-2-methyl-1,3-propanediol / methanol solution is added, and the reaction is carried out at room temperature for 10-15 hours, and then a saturated sodium bicarbonate aqueous solution is added, filtered, and dried to obtain a fluorine-containing compound; wherein the amount ratio of perfluorooctanoyl chloride, tetrahydrofuran, and 2-amino-2-methyl-1,3-propanediol / methanol solution is (8.6-17.2) g: (150-200) g: (10-20) mL; dicarboxylated polypropylene glycol, fluorine-containing compound, p-toluenesulfonic acid , N,N-dimethylacetamide, heated to 110-130°C in a nitrogen atmosphere, stirred for reaction for 3-5h, and after the reaction, rotary evaporation, washing, and drying were performed to obtain modified polypropylene glycol; wherein the mass ratio of dicarboxylated polypropylene glycol, fluorinated compound, p-toluenesulfonic acid, and N,N-dimethylacetamide is (10-20): (15-25): (0.07-0.1): (120-150); in the above process, maleic anhydride is ring-opened and reacted with the hydroxyl group of polypropylene glycol to obtain dicarboxylated polypropylene glycol; the acyl chloride of perfluorooctanoyl chloride reacts with the amino group of 2-amino-2-methyl-1,3-propanediol to obtain a long-chain fluorinated compound containing fluorine; the fluorinated compound is then reacted with the dicarboxylated polypropylene glycol through an ester reaction. The fluorine-containing chain is introduced into the polypropylene glycol by combining with the reaction of the modified polypropylene glycol; preferably, in the step (5), the preparation method of the high-performance polyurethane prepolymer is as follows: the modified polypropylene glycol, the functionalized bio-based polyol, acetone and isophorone diisocyanate are mixed, stirred at 75-85°C for 20-40 minutes, and then dibutyltin dilaurate is added, and the stirring is continued for 100-150 minutes to obtain a high-performance polyurethane prepolymer; wherein the mass ratio of the modified polypropylene glycol, the functionalized bio-based polyol, isophorone diisocyanate, dibutyltin dilaurate and acetone is (7.5-15): (2-6): (4.2-8.4): (0.03-0.05): (80-100). .
[0014] Preferably, in step (5), the contents of the components in the weather-resistant high-viscosity one-component composite glue are, by weight, 10-15 parts of high-performance polyurethane prepolymer, 10-15 parts of high-acid value acrylic resin, 1-5 parts of cellulose acetate butyrate, 1-5 parts of SBS rubber, 1.5-4.5 parts of multifunctional nanofiller, 1-3 parts of latent curing agent, and 57-75 parts of solvent; the solvent comprises at least one of ethyl acetate, propyl acetate, and butyl acetate; the acid value of the high-acid value acrylic resin is 9-11 mgKOH / g; and the latent curing agent comprises latent curing agent 4011.
[0015] Furthermore, in step (5), the method for preparing the multifunctional nanofiller comprises the following steps:
[0016] Step S1, mixing cerium (III) nitrate hexahydrate, calcium nitrate and deionized water, stirring until all solids are dissolved, adding polyvinyl pyrrolidone, stirring at 55-65° C. for 40-60 min, then adding 18.7-37.4 mL of 0.8 mol / L ammonium carbonate aqueous solution at a speed of 4-6 mL / min, stirring at a speed of 500-600 r / min for 4-6 h, filtering, washing, drying the obtained precipitate at 60-80° C., and then calcining at 590-610° C. for 100-150 min to obtain composite nanoparticles; wherein the mass ratio of cerium (III) nitrate hexahydrate, calcium nitrate, deionized water, polyvinyl pyrrolidone and ammonium carbonate aqueous solution is: (3.5-7) g: (0.3-0.6) g: (80-100) g: (0.1-0.2) g: (18.7-37.4) mL; γ-aminopropyltriethoxysilane and composite nanoparticles are dispersed in ethanol, and then refluxed for 4-6 hours at a temperature of 75-80°C and a pH of 4-10, and the precipitate is collected and dried to obtain surface-modified composite nanoparticles; wherein the mass ratio of γ-aminopropyltriethoxysilane, composite nanoparticles, and ethanol is (1-3): 10:80; in the above process, cerium oxide nanoparticles doped with calcium oxide, i.e. composite nanoparticles, are prepared by a coprecipitation method; and amino groups are introduced into the surface of the composite nanoparticles by modification with γ-aminopropyltriethoxysilane;
[0017] Step S2, thionyl chloride and graphene oxide are mixed in a mass ratio of (32.7-65.4): (1-1.5), heated to 55-65°C and maintained for 20-28 hours, and after the reaction is completed, the temperature is raised to 85-95°C to remove excess thionyl chloride to obtain modified graphene oxide; the modified graphene oxide is added to N,N-dimethylformamide, ultrasonically treated for 30-60 minutes, and then surface-modified composite nanoparticles are added, heated to 85-95°C and maintained for 20-28 hours, centrifuged, washed, and dried to obtain an inorganic composite nanomaterial; wherein the modified The mass ratio of graphene oxide, N,N-dimethylformamide, and surface-modified composite nanoparticles is (1-1.5): (80-100): (0.5-1); the inorganic composite nanomaterial is added to N,N-dimethylformamide, stirred for 20-40 minutes, and then 1,2-epoxy-5-hexene is added, heated to 75-85°C and stirred for reaction for 20-30 hours, filtered, washed, and dried to obtain a surface-modified inorganic composite nanomaterial; wherein the mass ratio of the inorganic composite nanomaterial, N,N-dimethylformamide, and 1,2-epoxy-5-hexene is (3- 6): (200-300): (1.5-3.5); add the surface modified inorganic composite nanomaterial to acetone, ultrasonically treat for 20-40 minutes, then add a 3 mol / L trimethoxysilane / acetone solution and a 2% chloroplatinic acid aqueous solution in a nitrogen atmosphere, heat to 45-55°C and stir to react for 20-30 hours, filter, wash, and dry to obtain a multifunctional nanofiller; wherein the mass ratio of the surface modified inorganic composite nanomaterial, acetone, trimethoxysilane / acetone solution, and chloroplatinic acid aqueous solution is (3-6) g: (100-120) g: (20-30) mL: (0.5-1) mL; In the above process, thionyl chloride reacts with the carboxyl group of graphene oxide to produce chlorination reaction, acyl chloride groups are introduced on the surface of graphene oxide, amino groups on the surface of surface-modified composite nanoparticles react with acyl chloride groups, and the composite nanoparticles are loaded on the graphene oxide to obtain inorganic composite nanomaterials; the inorganic composite nanomaterials are modified by 1,2-epoxy-5-hexene, and carbon-carbon double bonds are introduced on the surface, which can react with trimethoxysilane to connect the trimethoxysilane to the inorganic composite nanomaterials.
[0018] The weather-resistant high-viscosity one-component composite glue is prepared by the method for preparing the weather-resistant high-viscosity one-component composite glue.
[0019] Application of the weather-resistant high-viscosity single-component composite glue in multi-layer structure car covers.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: the weather-resistant high-viscosity one-component composite glue of the present invention avoids the problem of short service life of two-component glue, and its components include high-performance polyurethane prepolymer, high-acid value acrylic resin, cellulose acetate butyrate, SBS rubber, and multifunctional nanofiller: polyurethane is used as the matrix of the glue, and it has good compatibility with the TPU substrate layer in the multi-layer structure car cover, and the various groups in the high-performance polyurethane prepolymer of the present invention can form a strong interaction with the TPU substrate layer, so that the glue can be firmly attached to the TPU substrate layer, but the glue layer is simply made of polyurethane resin, the product performance cannot meet the requirements, and there will be delamination, mechanical properties, and weather resistance. In order to solve the problem of insufficient energy, yellowing-resistant polyurethane resin, cellulose acetate butyrate, high acid value acrylic resin and SBS rubber are selectively added. Among them, high acid value acrylic resin has excellent weather resistance. Adding it to the system can improve the weather resistance of the glue and enhance the overall performance. At the same time, the carboxyl functional group can produce covalent bonds with the carbamate group segments of TPU to form excellent adhesion fastness; cellulose acetate butyrate has the excellent UV resistance and high temperature resistance of cellulose acetate and the excellent moisture resistance and stability of cellulose butyrate; SBS rubber has the advantages of high tensile strength, small permanent deformation and good low temperature resistance, and is compatible with a variety of resins. Adding it to the system can give the glue better performance.
[0021] The high-performance polyurethane prepolymer of the present invention is obtained by reacting a functionalized bio-based polyol prepared from a bio-based material, acrylic pimaric acid, with modified polypropylene glycol and isophorone diisocyanate. The functionalized bio-based polyol and modified polypropylene glycol play an important role in improving the performance of the polyurethane prepolymer, which is specifically manifested in the following aspects: (1) the functionalized bio-based polyol is used as a part of the polyurethane chain, which not only improves the cross-linking density of the polyurethane system, but also introduces a variety of dynamic bonds (disulfide bonds, imine bonds, reversible coumarin rings), hydrogen bonds, π-π stacking, and polar phenanthrene rings into the polyurethane structure. The bonding force caused by the structure gives the polyurethane system excellent mechanical strength, viscosity, high temperature resistance and self-healing performance. At the same time, the polar phenanthrene ring also improves the flexibility of the polyurethane system and can improve the repair effect of dynamic bonds. In addition, the functionalized bio-based polyol also contains a magnolia phenol structure with a benzene ring and a phenolic hydroxyl group, which gives the polyurethane system anti-ultraviolet performance; (2) by introducing fluorine-containing chains into polypropylene glycol and hydrophobic chains into polyurethane satin, the cross-linking density of the polyurethane system is increased, and the polyurethane system is given good hydrophobicity. Therefore, the high-performance polyurethane prepolymer of the present invention has good mechanical properties, adhesion, weather resistance and self-healing properties.
[0022] In addition, the present invention adds a multifunctional nano filler to the weather-resistant high-viscosity single-component composite glue. The multifunctional nano filler of the present invention is obtained by loading cerium oxide nano particles doped with calcium oxide, that is, composite nano particles, on graphene oxide, and then grafting trimethoxysilane. After the cerium oxide nano particles are doped with calcium oxide, the particle size thereof will be reduced, thereby resulting in an improvement in the ultraviolet absorption and shielding capability, thereby improving the anti-ultraviolet performance of the glue; graphene oxide can extend the water penetration path due to its own heat resistance, mechanical properties and sheet structure, and improve the high temperature resistance, moisture and heat resistance and viscosity of the glue; loading the composite nano particles on graphene oxide can weaken the interaction between graphene oxide sheets and improve the dispersibility of graphene oxide. At the same time, graphene oxide can also be used as a dispersing platform for composite nano particles, so that the composite nano particles can also be better dispersed; further, trimethoxysilane is connected to the surface of the inorganic composite nano material to improve the dispersibility, high temperature resistance and hydrophobicity of the inorganic composite nano material, thereby improving the high temperature resistance, moisture and heat resistance and viscosity of the glue. Therefore, the multifunctional nano filler of the present invention can effectively improve the weather resistance and adhesion of the glue. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a process flow chart of the preparation method of the weather-resistant high-viscosity single-component composite glue of the present invention;
[0024] Figure 2 It is a schematic diagram of the synthesis of the intermediate product A of the present invention;
[0025] Figure 3 It is a schematic diagram of the synthesis of the intermediate product B of the present invention;
[0026] Figure 4 It is a schematic diagram of the synthesis of the intermediate product C of the present invention;
[0027] Figure 5 It is a comparison chart of lap shear strength tests of weather-resistant high-viscosity one-component composite glues prepared in Examples 2-4 of the present invention and Comparative Examples 3-7 under different conditions. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] This embodiment discloses a method for preparing a multifunctional nanofiller, comprising the following steps:
[0031] Step S1, 5.25g of cerium (III) nitrate hexahydrate, 0.45g of calcium nitrate, and 90g of deionized water are mixed, stirred until all solids are dissolved, and then 0.15g of polyvinyl pyrrolidone is added, and stirred at 60°C for 50min, and then 28mL of an aqueous solution of ammonium carbonate with a concentration of 0.8mol / L is added dropwise at a speed of 5mL / min, and stirred at a speed of 550r / min for 5h, filtered, washed, and the obtained precipitate is dried at 70°C, and then calcined at 600°C for 120min to obtain composite nanoparticles; 2g of γ-aminopropyltriethoxysilane and 10g of the composite nanoparticles are dispersed in 80g of ethanol, and then refluxed at a temperature of 78°C and a pH of 7 for 5h, and the precipitate is collected and dried to obtain surface-modified composite nanoparticles;
[0032] Step S2, 49.1g of thionyl chloride and 1.3g of graphene oxide are mixed, heated to 60°C and maintained for 24h, and after the reaction is completed, the temperature is raised to 90°C to remove excess thionyl chloride to obtain modified graphene oxide; 1.3g of modified graphene oxide is added to 890g of N,N-dimethylformamide, ultrasonically treated for 45min, and then 0.8g of surface-modified composite nanoparticles are added, heated to 90°C and maintained for 24h, centrifuged, washed, and dried to obtain an inorganic composite nanomaterial; 4.5g of the inorganic composite nanomaterial is added to 250g of N,N-dimethylformamide, stirred for 30min, and then 2.5g 1,2-Epoxy-5-hexene was heated to 80°C and stirred for 24 hours, filtered, washed, and dried to obtain a surface-modified inorganic composite nanomaterial; 4.5 g of the surface-modified inorganic composite nanomaterial was added to 110 g of acetone and ultrasonically treated for 30 minutes. In a nitrogen atmosphere, 25 mL of a 3 mol / L trimethoxysilane / acetone solution and 0.8 mL of a 2% chloroplatinic acid aqueous solution were added, and the mixture was heated to 50°C and stirred for 25 hours. The mixture was filtered, washed, and dried to obtain a multifunctional nanofiller.
[0033] Example 2
[0034] This embodiment discloses a method for preparing a weather-resistant high-viscosity one-component composite glue, comprising the following steps:
[0035] Step (1), 60g of rosin and 0.2g of hydroquinone are mixed, and the temperature is raised to 230°C at a rate of 5°C / min in a nitrogen atmosphere, and then 15g of acrylic acid is added dropwise at a rate of 0.8mL / min. After the addition is completed, the temperature is kept unchanged for 4h. After the reaction is completed, the nitrogen flow rate is increased to remove moisture and unreacted acrylic acid and other volatiles, and the temperature is lowered to 170°C, the material is discharged, cooled to room temperature, ground, washed, and dried to obtain propylene pimaric acid; 15g of propylene pimaric acid and 0.1g of triethylamine are added to 200g of tetrahydrofuran and mixed until uniform, and then 20g of oxalyl chloride is added, and the mixture is stirred at 4°C for 40min, and then stirred at 28°C for 3.5h. After the reaction is completed, the solid by-products are removed by suction filtration, and the obtained filtrate is subjected to reduced pressure distillation at 40°C to remove the solvent, and then washed with ethanol and dried to obtain chlorinated modified propylene pimaric acid; 6.2g of 4,4'-dithiodiphenylamine is added to 100g N,N-dimethylformamide was mixed until uniform, and then 4.9 g of acyl chloride modified acrylopimaric acid was added, and the mixture was heated to 85°C for reaction for 28 h. After the reaction was completed, the solvent was removed by rotary evaporation at 75°C to obtain intermediate product A;
[0036] Step (2), adding 5.3 g of magnolol to 200 g of ethanol, ultrasonically treating for 20 min, heating to 60° C., adding 3.5 g of 3-mercaptopropionic acid and 15 g of azobisisobutyronitrile / ethanol solution with a mass fraction of 0.5 wt%, stirring for 5 h, filtering, washing, and drying after the reaction is completed to obtain a magnolol derivative; mixing 8.8 g of hydroxymethylcoumarin, 7.6 g of 3,5-diaminobenzoic acid, 0.07 g of p-toluenesulfonic acid, and 120 g of N,N-dimethylformamide, heating to 120° C. in a nitrogen atmosphere, stirring for 5 h, and after the reaction is completed, removing the solvent by rotary evaporation at 75° C., and washing the obtained product with deionized water and drying to obtain an intermediate product B; adding 4.8 g of magnolol derivative to 80 g of ethanol, ultrasonically treating for 20 min, adding 3.7 g of N'N-dicyclohexyl diimide, 2.1 g N-hydroxysuccinimide was stirred for 1 hour, and then 6.2 g of intermediate product B was added under stirring conditions. The mixture was stirred and reacted at room temperature for 22 hours in a nitrogen atmosphere. During the reaction, the pH of the reaction system was adjusted to 5.4 with a 1 mol / L aqueous hydrochloric acid solution. After the reaction was completed, the mixture was filtered, washed, and dried to obtain intermediate product C;
[0037] Step (3), add 8.2g of intermediate product A to 200g of N,N-dimethylformamide, then add 1.5g of glutaraldehyde, heat to 90°C for reaction for 11h, then add 10.4g of intermediate product C, continue stirring and reacting for 10h, after the reaction is completed, rotary evaporate at 70°C to obtain intermediate product D; add 10g of intermediate product D to 200g of N,N-dimethylformamide, stir for 20min, then add 3.5g of 1-(2-oxirane-1,2-diol), heat to 60°C for reaction with stirring for 24h, rotary evaporate at 80°C to remove the solvent, wash the obtained product with ethanol, and dry to obtain functionalized bio-based polyol;
[0038] Step (4), adding 10g of polypropylene glycol to 200g of dichloromethane, then adding 4g of maleic anhydride and 0.05g of 4-dimethylaminopyridine, stirring and reacting at room temperature for 70h, after the reaction is completed, precipitating the product with ether, washing, and drying to obtain dicarboxylated polypropylene glycol; in a nitrogen atmosphere, adding 8.6g of perfluorooctanoyl chloride to 150g of tetrahydrofuran, then adding 10mL of 0.2g / mL 2-amino-2-methyl-1,3-propanediol / methanol solution, reacting at room temperature for 10h, then adding saturated sodium bicarbonate aqueous solution, filtering, and drying to obtain a fluorine-containing compound; mixing 10g of dicarboxylated polypropylene glycol, 15g of the fluorine-containing compound, 0.07g of p-toluenesulfonic acid, and 120g of N,N-dimethylacetamide, heating to 110°C in a nitrogen atmosphere, stirring and reacting for 3h, after the reaction is completed, rotary evaporating at 80°C, washing, and drying to obtain a modified polypropylene glycol;
[0039] Step (5), 7.5 g of modified polypropylene glycol, 2 g of functionalized bio-based polyol, 80 g of acetone, and 4.2 g of isophorone diisocyanate are mixed, stirred at 75° C. for 20 min, and then 0.03 g of dibutyltin dilaurate is added, and stirring is continued for 150 min. The solvent is evaporated to obtain a high-performance polyurethane prepolymer; in parts by weight, 10 parts of a high-performance polyurethane prepolymer, 10 parts of a high-acid value acrylic resin, 1 part of cellulose acetate butyrate, 1 part of SBS rubber, 1.5 parts of a multifunctional nanofiller, 1 part of a latent curing agent 4011, and 57 parts of ethyl acetate are mixed, and the mixture is sealed and stored at low temperature to obtain a weather-resistant high-viscosity one-component composite glue.
[0040] Example 3
[0041] This embodiment discloses a method for preparing a weather-resistant high-viscosity one-component composite glue, comprising the following steps:
[0042] Step (1), 100g of rosin and 0.5g of hydroquinone are mixed, and the temperature is raised to 240°C at a rate of 10°C / min in a nitrogen atmosphere, and then 30g of acrylic acid is added dropwise at a rate of 1.2mL / min. After the addition is completed, the temperature is kept unchanged for 4h. After the reaction is completed, the nitrogen flow rate is increased to remove moisture and unreacted acrylic acid and other volatiles, and the temperature is lowered to 180°C, the material is discharged, cooled to room temperature, ground, washed, and dried to obtain propylene pimaric acid; 25g of propylene pimaric acid and 0.15g of triethylamine are added to 300g of tetrahydrofuran and mixed until uniform, and then 40g of oxalyl chloride is added, and the mixture is stirred at 6°C for 20min, and then stirred at 32°C for 2.5h. After the reaction is completed, the solid by-products are removed by suction filtration, and the obtained filtrate is subjected to reduced pressure distillation at 50°C to remove the solvent, and then washed with ethanol and dried to obtain chlorinated modified propylene pimaric acid; 12.4g of 4,4'-dithiodiphenylamine is added to 150g N,N-dimethylformamide was mixed until uniform, and then 9.8g of acyl chloride modified acrylopimaric acid was added, and the mixture was heated to 95°C for reaction for 20h. After the reaction was completed, the solvent was removed by rotary evaporation at 85°C to obtain intermediate product A;
[0043] Step (2), adding 10.6 g of magnolol to 300 g of ethanol, ultrasonically treating for 40 min, heating to 70° C., adding 5.5 g of 3-mercaptopropionic acid and 20 g of azobisisobutyronitrile / ethanol solution with a mass fraction of 0.5 wt%, stirring for 3 h, filtering, washing, and drying after the reaction is completed to obtain a magnolol derivative; mixing 17.6 g of hydroxymethylcoumarin, 15.2 g of 3,5-diaminobenzoic acid, 0.1 g of p-toluenesulfonic acid, and 150 g of N,N-dimethylformamide, heating to 140° C. in a nitrogen atmosphere, stirring for 3 h, and after the reaction is completed, removing the solvent by rotary evaporation at 85° C., and washing the obtained product with deionized water and drying to obtain an intermediate product B; adding 9.6 g of magnolol derivative to 120 g of ethanol, ultrasonically treating for 40 min, adding 7.4 g of N'N-dicyclohexyldiimide, 4.2 g of N-hydroxysuccinimide was stirred for 2 h, and then 12.4 g of intermediate product B was added under stirring conditions. The mixture was stirred and reacted at room temperature for 26 h in a nitrogen atmosphere. During the reaction, the pH of the reaction system was adjusted to 5.6 with a 1 mol / L aqueous hydrochloric acid solution. After the reaction was completed, the mixture was filtered, washed, and dried to obtain intermediate product C.
[0044] Step (3), add 16.4 g of intermediate product A to 300 g of N,N-dimethylformamide, then add 4.5 g of glutaraldehyde, heat to 98 ° C for reaction for 9 h, then add 20.8 g of intermediate product C, continue stirring and reacting for 10 h, after the reaction is completed, rotary evaporate at 80 ° C to obtain intermediate product D; add 20 g of intermediate product D to 300 g of N,N-dimethylformamide, stir for 40 min, then add 5.5 g of 1-(2-oxirane-1,2-diol), heat to 80 ° C for reaction with stirring for 16 h, rotary evaporate at 80 ° C to remove the solvent, wash the obtained product with ethanol, and dry it to obtain a functionalized bio-based polyol;
[0045] Step (4), adding 20g of polypropylene glycol to 300g of dichloromethane, then adding 7g of maleic anhydride and 0.1g of 4-dimethylaminopyridine, stirring and reacting at room temperature for 80h, after the reaction is completed, precipitating the product with ether, washing, and drying to obtain dicarboxylated polypropylene glycol; in a nitrogen atmosphere, adding 17.2g of perfluorooctanoyl chloride to 200g of tetrahydrofuran, then adding 20mL of 0.2g / mL 2-amino-2-methyl-1,3-propanediol / methanol solution, reacting at room temperature for 15h, then adding saturated sodium bicarbonate aqueous solution, filtering, and drying to obtain a fluorine-containing compound; mixing 20g of dicarboxylated polypropylene glycol, 25g of the fluorine-containing compound, 0.1g of p-toluenesulfonic acid, and 150g of N,N-dimethylacetamide, heating to 130°C in a nitrogen atmosphere, stirring and reacting for 3h, after the reaction is completed, rotary evaporating at 90°C, washing, and drying to obtain a modified polypropylene glycol;
[0046] Step (5), 15 g of modified polypropylene glycol, 6 g of functionalized bio-based polyol, 100 g of acetone, and 8.4 g of isophorone diisocyanate were mixed, stirred at 85° C. for 20 min, and then 0.05 g of dibutyltin dilaurate was added, and the stirring was continued for 100 min. The solvent was evaporated to obtain a high-performance polyurethane prepolymer;
[0047] In parts by weight, 15 parts of high-performance polyurethane prepolymer, 15 parts of high-acid value acrylic resin, 5 parts of cellulose acetate butyrate, 5 parts of SBS rubber, 4.5 parts of multifunctional nanofiller, 3 parts of latent curing agent 4011, and 75 parts of ethyl acetate are mixed and stored in a sealed state at low temperature to obtain a weather-resistant and high-viscosity one-component composite glue.
[0048] Example 4
[0049] This embodiment discloses a method for preparing a weather-resistant high-viscosity one-component composite glue, comprising the following steps:
[0050] Step (1), 680g of rosin and 0.3g of hydroquinone are mixed, and the temperature is raised to 235°C at a rate of 7.5°C / min in a nitrogen atmosphere, and then 22.5g of acrylic acid is added dropwise at a rate of 1mL / min. After the addition is completed, the temperature is kept unchanged for 3.5h. After the reaction is completed, the nitrogen flow rate is increased to remove moisture and unreacted acrylic acid and other volatiles, and the temperature is reduced to 175°C, the material is discharged, cooled to room temperature, ground, washed, and dried to obtain propylene pimaric acid; 20g of propylene pimaric acid and 0.12g of triethylamine are added to 250g of tetrahydrofuran and mixed until uniform, and then 30g of oxalyl chloride is added, and the mixture is stirred at 5°C for 30min, and then stirred at 30°C for 3h. After the reaction is completed, the solid by-products are removed by suction filtration, and the obtained filtrate is subjected to reduced pressure distillation at 45°C to remove the solvent, and then washed with ethanol and dried to obtain chlorinated modified propylene pimaric acid; 9.3g of 4,4'-dithiodiphenylamine is added to 120g N,N-dimethylformamide was mixed until uniform, and then 7.4 g of acyl chloride modified acrylopimaric acid was added, and the mixture was heated to 90°C for reaction for 24 h. After the reaction was completed, the solvent was removed by rotary evaporation at 80°C to obtain intermediate product A;
[0051] Step (2), adding 7.9 g of magnolol to 250 g of ethanol, ultrasonically treating for 30 min, heating to 65° C., adding 4.5 g of 3-mercaptopropionic acid and 17.5 g of azobisisobutyronitrile / ethanol solution with a mass fraction of 0.5 wt%, stirring for 4 h, filtering, washing, and drying after the reaction is completed to obtain a magnolol derivative; mixing 13.2 g of hydroxymethylcoumarin, 11.4 g of 3,5-diaminobenzoic acid, 0.08 g of p-toluenesulfonic acid, and 135 g of N,N-dimethylformamide, heating to 130° C. in a nitrogen atmosphere, stirring for 4 h, after the reaction is completed, rotary evaporation at 80° C. to remove the solvent, and the obtained product is then washed with deionized water and dried to obtain an intermediate product B; adding 7.2 g of magnolol derivative to 100 g of ethanol, ultrasonically treating for 30 min, adding 5.6 g of N'N-dicyclohexyl diimide, 3.2 g of N-hydroxysuccinimide was stirred for 1.5 hours, and then 9.3 g of intermediate product B was added under stirring conditions. The mixture was stirred and reacted at room temperature for 24 hours in a nitrogen atmosphere. During the reaction, the pH of the reaction system was adjusted to 5.5 with a 1 mol / L aqueous hydrochloric acid solution. After the reaction was completed, the mixture was filtered, washed, and dried to obtain intermediate product C;
[0052] Step (3), add 12.3 g of intermediate product A to 250 g of N, N-dimethylformamide, then add 3 g of glutaraldehyde, heat to 94 ° C for reaction for 10 h, then add 15.6 g of intermediate product C, continue stirring and reacting for 13 h, after the reaction is completed, rotary evaporate at 75 ° C to obtain intermediate product D; add 15 g of intermediate product D to 250 g of N, N-dimethylformamide, stir for 30 min, then add 4.5 g of 1-(2-oxirane-1,2-diol), heat to 70 ° C for reaction with stirring for 20 h, rotary evaporate at 75 ° C to remove the solvent, wash the obtained product with ethanol, and dry it to obtain a functionalized bio-based polyol;
[0053] Step (4), add 15g of polypropylene glycol to 250g of dichloromethane, then add 5.5g of maleic anhydride and 0.08g of 4-dimethylaminopyridine, stir and react at room temperature for 75h, precipitate the product with ether after the reaction, wash and dry to obtain dicarboxylated polypropylene glycol; in a nitrogen atmosphere, add 12.9g of perfluorooctanoyl chloride to 175g of tetrahydrofuran, then add 15mL of 0.2g / mL 2-amino-2-methyl-1,3-propanediol / methanol solution, react at room temperature for 12h, then add saturated sodium bicarbonate aqueous solution, filter and dry to obtain a fluorine-containing compound; 15g of dicarboxylated polypropylene glycol, 20g of the fluorine-containing compound, 0.08g of p-toluenesulfonic acid, 135g N, N-dimethylacetamide was mixed, heated to 120°C in a nitrogen atmosphere, stirred and reacted for 4 hours, and after the reaction was completed, rotary evaporated at 85°C, washed, and dried to obtain modified polypropylene glycol;
[0054] Step (5), 11.2 g of modified polypropylene glycol, 4 g of functionalized bio-based polyol, 90 g of acetone, and 6.3 g of isophorone diisocyanate are mixed, stirred at 80° C. for 30 min, and then 0.04 g of dibutyltin dilaurate is added, and stirring is continued for 120 min. The solvent is evaporated to obtain a high-performance polyurethane prepolymer; in parts by weight, 12.5 parts of a high-performance polyurethane prepolymer, 12.5 parts of a high-acid value acrylic resin, 3 parts of cellulose acetate butyrate, 3 parts of SBS rubber, 2.8 parts of a multifunctional nanofiller, 2 parts of a latent curing agent 4011, and 66 parts of ethyl acetate are mixed, and the mixture is sealed and stored at low temperature to obtain a weather-resistant high-viscosity one-component composite glue.
[0055] The multifunctional nanofiller used in the above Examples 2-4 is the multifunctional nanofiller prepared in Example 1.
[0056] Comparative Example 1
[0057] Compared with Example 1, in the process of preparing the composite nanoparticles in Comparative Example 1, no calcium nitrate was added. The composite nanoparticles in this comparative example are cerium oxide nanoparticles, and other conditions remain unchanged.
[0058] Comparative Example 2
[0059] Compared with Example 1, in Comparative Example 2, in the process of preparing the surface-modified inorganic composite nanomaterial, graphene oxide is used instead of the inorganic composite nanomaterial, and other conditions remain unchanged.
[0060] Comparative Example 3
[0061] Compared with Example 4, Comparative Example 3 uses the multifunctional nanofiller prepared in Comparative Example 1, and other conditions remain unchanged.
[0062] Comparative Example 4
[0063] Compared with Example 4, Comparative Example 4 uses the multifunctional nanofiller prepared in Comparative Example 2, and other conditions remain unchanged.
[0064] Comparative Example 5
[0065] Compared with Example 4, in the process of preparing the weather-resistant high-viscosity one-component composite glue in Comparative Example 5, the surface-modified inorganic composite nanomaterial is used instead of the multifunctional nanofiller, and other conditions remain unchanged.
[0066] Comparative Example 6
[0067] Compared with Example 4, in Comparative Example 6, during the preparation of the high-performance polyurethane prepolymer, polypropylene glycol was used instead of modified polypropylene glycol, and other conditions remained unchanged.
[0068] Comparative Example 7
[0069] Compared with Example 4, in the process of preparing functionalized bio-based polyols in Comparative Example 7, intermediate product A was used instead of intermediate product C, and other conditions remained unchanged.
[0070] In the above embodiments and comparative examples, rosin, acid value 177 mgKOH / g, from Guangxi Wuzhou Rosin Co., Ltd.; magnolol, boiling point 401 ° C (760 mmHg), density 1.107 g / cm3, melting point 101-102 ° C, from Hubei Xinghengye Technology Co., Ltd.; polypropylene glycol, Mn = 2000 g / mol, from Jiangsu Hai'an Petrochemical Plant; graphene oxide, sheet diameter 0.5-5 μm, graphene oxide layer number 1-6 layers, from Beijing Beike New Materials Technology Co., Ltd.; high acid value acrylic resin: brand Dow, grade B-48N, glass transition temperature 50 ° C, viscosity 800 mPas, acid value 11 mg KOH / g, from Dongguan Haosheng Plastic Raw Materials Co., Ltd.; cellulose acetate butyrate: molecular weight 30,000, from (Kramer) Shanghai Puzhen Biotechnology Co., Ltd.; SBS rubber is styrene butadiene rubber, which is a polystyrene butadiene copolymer with a tensile strength of 24Mpa and an elongation at break ≥730%. The model is SBS-792E, and the brand is Baling Petrochemical, from Guangdong Dingxin Polymer Technology Co., Ltd.; latent curing agent 4011, with an active ingredient content of 99%, comes from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0071] Experimental example
[0072] The performance of the weather-resistant high-viscosity one-component composite glue prepared in Examples 2-4 and Comparative Examples 3-7 was tested.
[0073] 1. Adhesion performance test: According to GB / T 7124-2008, lap shear test was carried out to detect the adhesion performance of each group of samples at room temperature.
[0074] 2. Weather resistance test:
[0075] (1) Hygrothermal aging: Place the sample in a constant temperature and humidity test chamber at a temperature of 50°C and a relative humidity of 95% for 90 days to test the lap shear strength;
[0076] (2) Thermal aging: Immerse the specimen in a constant temperature water bath at 95°C for 7 days and test the lap shear strength;
[0077] (3) Yellowing resistance: UV aging 30KWH / m 2 .
[0078] 3. Self-repairing performance test: Test the elongation at break according to the method specified in GB / T 528-2009. Cut the dumbbell spline from the middle of the gauge section, splice it, and treat it in a 40℃ oven for 6 hours to test the elongation at break. The self-repairing efficiency is evaluated by the retention rate of the elongation at break.
[0079] The test results are shown in Table 1:
[0080]
[0081] It can be seen from the test results in Table 1 that the weather-resistant high-viscosity one-component composite glue prepared in Examples 2-4 of the present invention has the advantages of high viscosity, good weather resistance and self-repairing performance.
[0082] From the comparison between comparative examples 3-4 and example 4, it can be seen that after the cerium oxide nanoparticles are doped with calcium oxide, their particle size will be reduced, thereby improving the ultraviolet absorption and shielding ability, thereby improving the anti-ultraviolet performance of the glue, and loading the composite nanoparticles on graphene oxide can weaken the interaction between graphene oxide sheets, improve the dispersibility of graphene oxide, thereby improving the weather resistance and viscosity of the glue; from the comparison between comparative example 5 and example 4, it can be seen that trimethoxysilane is introduced on the surface of the inorganic composite nanomaterial to improve the dispersibility, high temperature resistance and hydrophobicity of the inorganic composite nanomaterial, thereby improving the high temperature resistance, ultraviolet resistance, moisture and heat resistance and Viscosity; From the comparison between Comparative Example 6 and Example 4, it can be seen that by introducing fluorine-containing chains into polypropylene glycol and hydrophobic chains into polyurethane satin, the crosslinking density of the polyurethane system is increased while giving the polyurethane system good hydrophobicity. The increase in crosslinking density means the improvement of the overall performance of the polyurethane system; From the comparison between Comparative Example 7 and Example 4, it can be seen that the intermediate product C makes the chain structure of the functionalized bio-based polyol longer, increases the crosslinking density of the polyurethane, and introduces a reversible coumarin ring, magnolol structure and hydrogen bond into the polyurethane, thereby improving the viscosity, high temperature resistance, moisture and heat resistance, UV resistance and self-healing performance of the polyurethane system.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a weather-resistant high-viscosity one-component composite glue, characterized in that: The following steps are involved: Step (1), using rosin, hydroquinone and acrylic acid as raw materials to prepare acrylpimaric acid; wherein the mass ratio of rosin, hydroquinone and acrylic acid is (60-100): (0.2-0.5): (15-30); after acrylpimaric acid is reacted with triethylamine, tetrahydrofuran and oxalyl chloride to achieve chlorination modification, it is reacted with 4,4'-dithiodiphenylamine and N,N-dimethylformamide to obtain an intermediate product A; wherein the mass ratio of acrylpimaric acid, triethylamine, tetrahydrofuran and oxalyl chloride is (15-25): (0.1-0.15): (200-300): (20-40), and the mass ratio of 4,4'-dithiodiphenylamine, N,N-dimethylformamide and chlorination modified acrylpimaric acid is (6.2-12.4): (100-150): (4.9-9.8); Step (2), magnolol reacts with 3-mercaptopropionic acid, ethanol, and azobisisobutyronitrile / ethanol solution to obtain a magnolol derivative; wherein the mass ratio of magnolol, ethanol, 3-mercaptopropionic acid, and azobisisobutyronitrile / ethanol solution is (5.3-10.6): (200-300): (3.5-5.5): (15-20); hydroxymethylcoumarin reacts with 3,5-diaminobenzoic acid, p-toluenesulfonic acid, and N,N-dimethylformamide to obtain an intermediate product B; wherein hydroxymethylcoumarin, 3,5-diaminobenzoic acid, p-toluenesulfonic acid, and N,N-dimethylformamide are The mass ratio of the amide is (8.8-17.6): (7.6-15.2): (0.07-0.1): (120-150); the intermediate product B reacts with a magnolol derivative, ethanol, N'N-dicyclohexyl diimide, and N-hydroxysuccinimide to obtain an intermediate product C; wherein the mass ratio of the magnolol derivative, ethanol, N'N-dicyclohexyl diimide, N-hydroxysuccinimide, and the intermediate product B is (4.8-9.6): (80-120): (3.7-7.4): (2.1-4.2): (6.2-12.4); Step (3), adding intermediate product A to N,N-dimethylformamide, then adding glutaraldehyde, heating to 90-98°C for reaction for 9-11h, then adding intermediate product C, stirring and reacting for 10-16h, after the reaction is completed, rotary evaporation to obtain intermediate product D; wherein the mass ratio of intermediate product A, N,N-dimethylformamide, glutaraldehyde, and intermediate product C is (8.2-16.4): (200-300): (1.5-4.5): (10.4-20.8); then adding intermediate product C to the mixture, stirring and reacting for 10-16h, and then rotary evaporation to obtain intermediate product D; wherein the mass ratio of intermediate product A, N,N-dimethylformamide, glutaraldehyde, and intermediate product C is (8.2-16.4): (200-300): (1.5-4.5): (10.4-20.8); then The intermediate product D is added to N,N-dimethylformamide, stirred for 20-40 minutes, and then 1-(oxirane-2-yl)ethane-1,2-diol is added, heated to 60-80°C and stirred for reaction for 16-24 hours, rotary evaporated, washed, and dried to obtain functionalized bio-based polyols; wherein the mass ratio of the intermediate product D, N,N-dimethylformamide, and 1-(oxirane-2-yl)ethane-1,2-diol is (10-20): (200-300): (3.5-5.5); Step (4), perfluorooctanoyl chloride reacts with 2-amino-2-methyl-1,3-propanediol / methanol solution and tetrahydrofuran to obtain a fluorine-containing compound; wherein the amount ratio of perfluorooctanoyl chloride, tetrahydrofuran and 2-amino-2-methyl-1,3-propanediol / methanol solution is (8.6-17.2) g: (150-200) g: (10-20) mL; polypropylene glycol is carboxylated by reacting with dichloromethane, maleic anhydride and 4-dimethylaminopyridine to obtain dicarboxylated polypropylene glycol; wherein polypropylene glycol , dichloromethane, maleic anhydride, 4-dimethylaminopyridine in a mass ratio of (10-20): (200-300): (4-7): (0.05-0.1); dicarboxylated polypropylene glycol reacts with a fluorinated compound, p-toluenesulfonic acid, and N,N-dimethylacetamide to obtain modified polypropylene glycol; wherein the mass ratio of dicarboxylated polypropylene glycol, fluorinated compound, p-toluenesulfonic acid, and N,N-dimethylacetamide is (10-20): (15-25): (0.07-0.1): (120-150); Step (5), using modified polypropylene glycol, functionalized bio-based polyol, isophorone diisocyanate, dibutyltin dilaurate, and acetone as raw materials to prepare a high-performance polyurethane prepolymer; wherein the mass ratio of modified polypropylene glycol, functionalized bio-based polyol, isophorone diisocyanate, dibutyltin dilaurate, and acetone is (7.5-15): (2-6): (4.2-8.4): (0.03-0.05): (80-100); mixing a high-performance polyurethane prepolymer, a high-acid value acrylic resin, cellulose acetate butyrate, SBS rubber, a multifunctional nanofiller, a solvent, and a latent curing agent, and storing the mixture in a sealed container at low temperature to obtain a weather-resistant high-viscosity single-component composite glue; wherein the preparation method of the multifunctional nanofiller comprises the following steps: Step S1, using cerium (III) nitrate hexahydrate, calcium nitrate, and de- Composite nanoparticles are prepared using ionized water, polyvinyl pyrrolidone and ammonium carbonate aqueous solution as raw materials, wherein the mass ratio of cerium (III) nitrate hexahydrate, calcium nitrate, deionized water, polyvinyl pyrrolidone and ammonium carbonate aqueous solution is (3.5-7) g: (0.3-0.6) g: (80-100) g: (0.1-0.2) g: (18.7-37.4) mL; then the surface-modified composite nanoparticles are obtained by modifying them with γ-aminopropyltriethoxysilane; step S2, graphene oxide is modified with thionyl chloride and then combined with the surface-modified composite nanoparticles to obtain an inorganic composite nanomaterial; the inorganic composite nanomaterial reacts with 1,2-epoxy-5-hexene to obtain a surface-modified inorganic composite nanomaterial; the surface-modified inorganic composite nanomaterial reacts with trimethoxysilane to obtain a multifunctional nanofiller.
2. The method for preparing the weather-resistant high-viscosity one-component composite glue according to claim 1, characterized in that: In the step (1), the preparation method of the intermediate product A is as follows: rosin and hydroquinone are mixed, and the temperature is raised to 230-240°C at a rate of 5-10°C / min in a nitrogen atmosphere, and acrylic acid is then added dropwise at a rate of 0.8-1.2 mL / min. After the addition is completed, the temperature is kept constant for reaction for 3-4 hours. After the reaction is completed, the nitrogen flow rate is increased, the temperature is lowered to 170-180°C, the material is discharged, cooled to room temperature, ground, washed, and dried to obtain propylene pimaric acid; Add acrylpimaric acid and triethylamine to tetrahydrofuran and mix until uniform, then add oxalyl chloride, stir at 4-6°C for 20-40 minutes, then stir at 28-32°C for 2.5-3.5 hours, and purify after the reaction to obtain acyl chloride modified acrylpimaric acid; Add 4,4'-dithiodiphenylamine to N,N-dimethylformamide and mix until uniform, then add acyl chloride modified acrylopimaric acid, heat to 85-95°C and react for 20-28h. After the reaction is completed, perform rotary evaporation to obtain intermediate product A.
3. The method for preparing the weather-resistant high-viscosity one-component composite glue according to claim 1, characterized in that: In the step (2), the preparation method of the intermediate product C is as follows: adding magnolol to ethanol, ultrasonically treating for 20-40 minutes, heating to 60-70° C., then adding 3-mercaptopropionic acid and 0.5wt% azobisisobutyronitrile / ethanol solution, stirring for 3-5 hours, filtering, washing and drying after the reaction to obtain a magnolol derivative; Mix hydroxymethylcoumarin, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and N,N-dimethylformamide, heat to 120-140°C in a nitrogen atmosphere, stir and react for 3-5 hours, and purify after the reaction to obtain intermediate product B; A magnolol derivative is added to ethanol, ultrasonically treated for 20-40 minutes, N'N-dicyclohexyl diimide and N-hydroxysuccinimide are added, stirred for 1-2 hours, and then the intermediate product B is added under stirring conditions. The reaction is stirred at room temperature in a nitrogen atmosphere for 22-26 hours. During the reaction, the pH of the reaction system is adjusted to 5.4-5.6 with a 1 mol / L hydrochloric acid aqueous solution. After the reaction is completed, the reaction is filtered, washed, and dried to obtain the intermediate product C.
4. The method for preparing the weather-resistant high-viscosity one-component composite glue according to claim 1, characterized in that: In the step (4), the preparation method of the modified polypropylene glycol is as follows: polypropylene glycol is added to dichloromethane, and then maleic anhydride and 4-dimethylaminopyridine are added, and the mixture is stirred at room temperature for 70-80 hours. After the reaction is completed, the product is precipitated with ether, washed, and dried to obtain dicarboxylated polypropylene glycol; In a nitrogen atmosphere, perfluorooctanoyl chloride is added to tetrahydrofuran, and then a 0.2 g / mL 2-amino-2-methyl-1,3-propanediol / methanol solution is added, and the mixture is reacted at room temperature for 10-15 hours, and then a saturated sodium bicarbonate aqueous solution is added, filtered, and dried to obtain a fluorine-containing compound; wherein, The dicarboxylated polypropylene glycol, fluorine-containing compound, p-toluenesulfonic acid and N,N-dimethylacetamide are mixed, heated to 110-130° C. in a nitrogen atmosphere, and stirred for reaction for 3-5 hours. After the reaction is completed, the mixture is rotary evaporated, washed and dried to obtain modified polypropylene glycol.
5. The method for preparing the weather-resistant high-viscosity one-component composite glue according to claim 1, characterized in that: In the step (5), the preparation method of the high-performance polyurethane prepolymer is as follows: modified polypropylene glycol, functionalized bio-based polyol, acetone, and isophorone diisocyanate are mixed, stirred at 75-85° C. for 20-40 minutes, and then dibutyltin dilaurate is added, and stirring is continued for 100-150 minutes to obtain a high-performance polyurethane prepolymer.
6. The method for preparing the weather-resistant high-viscosity one-component composite glue according to claim 1, characterized in that: In the step (5), the contents of the components in the weather-resistant high-viscosity one-component composite glue are, by weight, 10-15 parts of high-performance polyurethane prepolymer, 10-15 parts of high-acid value acrylic resin, 1-5 parts of cellulose acetate butyrate, 1-5 parts of SBS rubber, 1.5-4.5 parts of multifunctional nanofiller, 1-3 parts of latent curing agent, and 57-75 parts of solvent; the solvent comprises at least one of ethyl acetate, propyl acetate, and butyl acetate; the acid value of the high-acid value acrylic resin is 9-11 mg KOH / g; and the latent curing agent comprises latent curing agent 4011.
7. The method for preparing the weather-resistant high-viscosity one-component composite glue according to claim 1, characterized in that: In step (5), the method for preparing the multifunctional nanofiller specifically comprises the following steps: Step S1, mixing cerium (III) nitrate hexahydrate, calcium nitrate and deionized water, stirring until all solids are dissolved, adding polyvinyl pyrrolidone, stirring at 55-65° C. for 40-60 min, then adding 18.7-37.4 mL of 0.8 mol / L ammonium carbonate aqueous solution dropwise at a speed of 4-6 mL / min, stirring at a speed of 500-600 r / min for 4-6 h, filtering, washing, drying the obtained precipitate at 60-80° C., and then calcining at 590-610° C. for 100-150 min to obtain composite nanoparticles; Dispersing γ-aminopropyltriethoxysilane and composite nanoparticles in ethanol, then reflux for 4-6 hours at a temperature of 75-80° C. and a pH of 4-10, collecting and drying the precipitate to obtain surface-modified composite nanoparticles; wherein the mass ratio of γ-aminopropyltriethoxysilane, composite nanoparticles, and ethanol is (1-3):10:80; Step S2, mixing thionyl chloride and graphene oxide in a mass ratio of (32.7-65.4): (1-1.5), heating to 55-65°C and maintaining for 20-28 hours, and after the reaction is completed, heating to 85-95°C to remove excess thionyl chloride to obtain modified graphene oxide; adding the modified graphene oxide to N,N-dimethylformamide, ultrasonically treating for 30-60 minutes, then adding surface-modified composite nanoparticles, heating to 85-95°C and maintaining for 20-28 hours, centrifuging, washing, and drying to obtain an inorganic composite nanomaterial; wherein the mass ratio of modified graphene oxide, N,N-dimethylformamide, and surface-modified composite nanoparticles is (1-1.5): (80-100): (0.5-1); Add the inorganic composite nanomaterial to N,N-dimethylformamide, stir for 20-40 minutes, then add 1,2-epoxy-5-hexene, heat to 75-85°C and stir for 20-30 hours, filter, wash and dry to obtain the surface-modified inorganic composite nanomaterial; wherein the mass ratio of the inorganic composite nanomaterial, N,N-dimethylformamide and 1,2-epoxy-5-hexene is (3-6): (200-300): (1.5-3.5); The surface modified inorganic composite nanomaterial is added to acetone, ultrasonically treated for 20-40 minutes, and then a 3 mol / L trimethoxysilane / acetone solution and a 2% by mass chloroplatinic acid aqueous solution are added in a nitrogen atmosphere, heated to 45-55°C and stirred for reaction for 20-30 hours, filtered, washed, and dried to obtain a multifunctional nanofiller; wherein the mass ratio of the surface modified inorganic composite nanomaterial, acetone, trimethoxysilane / acetone solution, and chloroplatinic acid aqueous solution is (3-6) g: (100-120) g: (20-30) mL: (0.5-1) mL.
8. A weather-resistant high-viscosity one-component composite glue prepared by the method for preparing a weather-resistant high-viscosity one-component composite glue as described in any one of claims 1 to 7.
9. Use of the weather-resistant high-viscosity one-component composite glue according to claim 8 in multi-layer structure car covers.
Citation Information
Patent Citations
A high-strength, yellowing-resistant elastic polyurethane adhesive, its preparation method and application
CN102295906A
Bio-based unsaturated polyester cured product and preparation method thereof
CN102977265A